(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
A personal instrumental analysis of the film “Rampage: Devastation” is presented, reflecting on it as an instrument for ideological communication by considering it as a symptomatic element of processes of a social nature, with the possibility of also using its professional nature analysis, by giving it a public health approach under the vision of the One Health paradigm.